Teacher Competencies, The Shortage of School Resources and Mathematics Achievement Based on PISA 2018 Indonesia - Hilmi, Irfan; Kismiantini (Mathematics Education Journal, 2024)
Investigating the low mathematics scores of Indonesian students on the PISA assessment can be done by examining the influence of measured predictors, including teacher competence and school resources that have not attracted the attention of Indonesian mathematics education researchers. The research focused on the effect of teacher competencies and the shortage of school resources on students’ mathematics achievement. Secondary data were retrieved from the official PISA website, involving 9,721 students aged 13-15 years from 332 schools after deleting the missing data. All students and schools were recruited using a stratified-two stage sample design and did not meet the exclusion criteria. Multilevel analysis was used to determine the significance of predictors of interest on students’ mathematics achievement. The analysis showed that adaptive teaching, teacher emotional support and teacher enthusiasm contributed to increase students’ mathematics achievement while teacher feedback and the shortage of school resources significantly decreased students’ mathematics achievement. These findings can assist policymakers in setting educational priorities especially related to what teacher competencies should be developed and procurement of school resources.